Iterative algorithm and estimation of solution for a fractional order differential equation - Wu, J.; Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Wiwatanapataphee, Benchawan (SpringerOpen, 2016)
In this paper, we establish an iterative algorithm and estimation of solutions for a fractional turbulent flow model in a porous medium under a suitable growth condition. Our main tool is the monotone iterative technique.